An Efficacy Trial of Recombinant Hepatitis E(rHEV) Vaccine in the Royal Nepalese Army - Shrestha, Mrigendra P (Medical Journal of Shree Birendra Hospital, 2002)
An Efficacy Trial of Recombinant Hepatitis E(rHEV) Vaccine in the Royal Nepalese Army